Efficacy and Safety of Rituximab in Chinese Children With Refractory Anti-NMDAR Encephalitis - Dou, Xiangjun; Li, Dongjing; Wu, Yan; Wang, Zhijing; Yang, Le; Ma, Nan; Wang, Dong; Li, Xia (Frontiers in Neurology, 2020)
Purpose: To assess the efficacy and safety of rituximab treatment as second-line immunotherapy in pediatric cases of anti-NMDA receptor (NMDAR) encephalitis. Methods: We retrospectively recruited 8 patients with anti-NMDAR encephalitis who were treated with rituximab as second-line immunotherapy. We evaluated the clinical features, laboratory examination results and treatment protocols of the Chinese children and defined good outcomes based on the modified Rankin scale (mRS) score (0–2) at the last follow-up. Results: A total of 8 pediatric patients (median age 6.7 years; 4 female) with refractory anti-NMDAR encephalitis were recruited to the study. Rituximab was given after a median duration of disease of 57 days (range 50.5–113.75 days). The use of rituximab led to a significant reduction in the mRS and CD19+ B-cells compared to before rituximab infusion (P < 0.05). 5 patients (62.5%) had a good outcome (mRS ≤ 2) including 4 patients (50%) who showed complete recovery (mRS = 0) at the last follow-up. Transient infusion adverse events were recorded in 2 patients (25%). Two patients (25%) had severe infectious adverse events (AEs) and 2 patients with grade 5 (death). None of the patients developed progressive multifocal leukoencephalopathy (PML). Conclusion: Our study provides evidence that rituximab can efficiently improve the clinical symptoms of anti-NMDAR encephalitis in children. However, due to the risk of adverse infections, rituximab should be restricted in pediatric patients with high rates of mortality and disability.